Compassion Fatigue: An Application of the Concept to Informal Caregivers of Family Members with Dementia - Jennifer R. Day; Ruth A. Anderson (Nursing Research and Practice)
Introduction. Compassion fatigue is a concept used with increasing frequency in the nursing literature. The objective of this paper is to identify common themes across the literature and to apply these themes, and an existing model of compassion fatigue, to informal caregivers for family members with dementia. Findings. Caregivers for family members with dementia may be at risk for developing compassion fatigue. The model of compassion fatigue provides an informative framework for understanding compassion fatigue in the informal caregiver population. Limitations of the model when applied to this population were identified as traumatic memories and the emotional relationship between parent and child, suggesting areas for future research. Conclusions. Research is needed to better understand the impact of compassion fatigue on informal caregivers through qualitative interviews, to identify informal caregivers at risk for compassion fatigue, and to provide an empirical basis for developing nursing interventions for caregivers experiencing compassion fatigue.